2(4x+7)+6x=5(x+10)

Simple and best practice solution for 2(4x+7)+6x=5(x+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4x+7)+6x=5(x+10) equation:


Simplifying
2(4x + 7) + 6x = 5(x + 10)

Reorder the terms:
2(7 + 4x) + 6x = 5(x + 10)
(7 * 2 + 4x * 2) + 6x = 5(x + 10)
(14 + 8x) + 6x = 5(x + 10)

Combine like terms: 8x + 6x = 14x
14 + 14x = 5(x + 10)

Reorder the terms:
14 + 14x = 5(10 + x)
14 + 14x = (10 * 5 + x * 5)
14 + 14x = (50 + 5x)

Solving
14 + 14x = 50 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
14 + 14x + -5x = 50 + 5x + -5x

Combine like terms: 14x + -5x = 9x
14 + 9x = 50 + 5x + -5x

Combine like terms: 5x + -5x = 0
14 + 9x = 50 + 0
14 + 9x = 50

Add '-14' to each side of the equation.
14 + -14 + 9x = 50 + -14

Combine like terms: 14 + -14 = 0
0 + 9x = 50 + -14
9x = 50 + -14

Combine like terms: 50 + -14 = 36
9x = 36

Divide each side by '9'.
x = 4

Simplifying
x = 4

See similar equations:

| -20+n=3.50 | | (6d+5)-(23d)= | | 5/4-1/3x1/2 | | 11=2x-11 | | -34+2x-7x=76 | | -5x+12=-12x+-12 | | 9-1/3a=-4 | | .25n=-12 | | 2x-9+x+3=-27 | | 4x-3=2(X+13) | | 2x-9+n+3=-27 | | -5x+12=-5x+-12 | | 16Y-7y=500 | | 4x-3+0=-3x-4 | | ((12k^2h)-(3kh^2))/3kh | | 0.25(8-4p)+2p=12 | | 2x+19y=300 | | 60=x+71 | | -3(6-8n)=-138 | | 35-6x=13+5x | | 5(x-2)-8x=-16 | | 8-15=3/7b | | (x)(30-2x)(16-2x)=0 | | 3/5y= | | -16(2.5)+13= | | 23=8n-5+6+3n | | 1/5-8/15 | | a+6(3a+4)=119 | | -5/7*8 | | 8(x-9)-5(x-9)=27 | | 3xy-4z=2x+10 | | -15=3(-2+x) |

Equations solver categories